2009
DOI: 10.1002/jgm.1387
|View full text |Cite
|
Sign up to set email alerts
|

FK506 as an adjuvant of tolerogenic DNA vaccination for the prevention of experimental autoimmune encephalomyelitis

Abstract: DNA vaccination, when applied with an immunosuppressant as adjuvant, can induce antigen-specific tolerance and prevent autoimmune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Addition of antigen specificity to such an approach may reduce undesired side effects associated with global immunosuppression that accompanies many of the current immunomodulatory therapies available (4-7). Indeed, several groups have begun investigating antigen-specific immunotherapies to treat autoimmune disorders (22)(23)(24)(25)(26)(27)(28)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of antigen specificity to such an approach may reduce undesired side effects associated with global immunosuppression that accompanies many of the current immunomodulatory therapies available (4-7). Indeed, several groups have begun investigating antigen-specific immunotherapies to treat autoimmune disorders (22)(23)(24)(25)(26)(27)(28)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DNA vaccination may activate different effectors including cytotoxic responses and autoantibody production which can lead to different effect of DNA vaccination on EAE prevention and treatment [19]. We previously found naïve mice immunized with p2MOG35/FK506 markedly impaired the Th17/Th1 responses and increased Th2 responses for EAE prevention [4]. In present study, p2MOG35/FK506 treatment of EAE mice suppressed Th17/Th1 cells responses consistently while Th2 cells responses was not enhanced.…”
Section: Discussionmentioning
confidence: 44%
“…FK506, as immunosuppressive agent, effectively promoted immunologic tolerance [19]. We previously found that naïve mice immunized with p2MOG35/FK506 induced Treg cells and effectively prevented EAE [4]. Here, the relevance of these findings was established for EAE treatment, in which p2MOG35/FK506 also augmented the induction of Treg cells and resulted in amelioration of EAE.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This concept and its potential application to trigger self-tolerance in autoimmune diseases were conceived by Kang et al [130]. These authors validated this hypothesis by demonstrating that FK506 (tacrolimus) associated with MOG was prophylactic in encephalomyelitis [131]. In this context, we hypothesized that active VitD could also behave as a tolerogenic adjuvant if associated with a CNS-specific antigen.…”
Section: Prophylactic Effect Of Vitd On Eaementioning
confidence: 78%